Avaliação dos transtornos do sono em pacientes com Covid longo: caracterização clínica, epidemiológica e relação temporal em uma coorte de pacientes ambulatorial - Moura, Alissa Elen Formiga (2023)
: Long-term COVID or post-COVID syndrome results from the persistence of symptoms or development of sequelae beyond 12 weeks after the onset of symptoms, a consequence of medium and long-term COVID-19. This condition can affect up to 32% of individuals infected with COVID-19, with symptoms of fatigue, dyspnea, chest pain, cognitive disorders, insomnia and psychiatric disorders. Objective: to characterize sleep disorders in a cohort of patients with long COVID. Methodology: this is an observational, longitudinal, prospective clinical study in patients diagnosed with COVID-19, who had symptoms related to sleep after the onset of the disease. Results: A total of 207 patients were initially evaluated, after the inclusion criteria, 189 patients participated in the long COVID sample, 48 (25.3%) had sleep disorder. Insomnia was reported by 42 patients (22.2%) and excessive sleepiness (SE) by 6 patients (3.17%). Four patients with SE were evaluated with polysomnography (PSG), actigraphy and multiple sleep latency testing (TMLS). Two patients were diagnosed with central hypersonia and one with narcolepsy. The use of corticosteroids was related to sleep complaints (insomnia and depression), while depression was related to excessive sleepiness. After 1 year of initial evaluation, patients with sleep disorder were reassessed. A total of 39 patients underwent new care, where 9 (28.2%) persisted with insomnia and 2 (5.12%) persisted with hypersonia of central origin. There is also a greater persistence of cognitive symptoms in patients who persisted with insomnia. Conclusion: Sleep-related complaints, such as insomnia and excessive sleepiness, are part of the long COVID syndrome, making up part of its clinical spectrum. This study suggests, therefore, the need for health professionals' attention to sleep complaints, still underestimated, in patients who persist with symptoms after acute COVID-19 infection.